IL-10 down-regulates costimulatory molecules on Mycobacterium tuberculosis-pulsed macrophages and impairs the lytic activity of CD4 and CD8 CTL in tuberculosis patients - de la Barrera, Silvia Susana (2004)
Activation of T cells requires both TCR-specific ligation and costimulation through accessory molecules during T cell priming. IFNγ is a key cytokine responsible for macrophage activation during Mycobacterium tuberculosis (Mtb) infection while IL-10 is associated with suppression of cell mediated immunity in intracellular infection. In this paper we evaluated the role of IFNγ and IL-10 on the function of cytotoxic T cells (CTL) and on the modulation of costimulatory molecules in healthy controls and patients with active tuberculosis (TB). γ-irradiated-Mtb (i-Mtb) induced IL-10 production from CD14+ cells from TB patients. Moreover, CD3+ T cells of patients with advanced disease also produced IL-10 after i-Mtb stimulation. In healthy donors, IL-10 decreased the lytic activity of CD4+ and CD8+ T cells whereas it increased γδ-mediated cytotoxicity. Furthermore, we found that the presence of IL-10 induced a loss of the alternative processing pathways of antigen presentation along with a down-regulation of the expression of costimulatory molecule expression on monocytes and macrophages from healthy individuals. Conversely, neutralization of endogenous IL-10 or addition of IFNγ to either effector or target cells from TB patients induced a strong lytic activity mediated by CD8+ CTL together with an up-regulation of CD54 and CD86 expression on target cells. Moreover, we observed that macrophages from TB patients could use alternative pathways for i-Mtb presentation. Taken together, our results demonstrate that the presence of IL-10 during Mtb infection might contribute to mycobacteria persistence inside host macrophages through a mechanism that involved inhibition of MHC-restricted cytotoxicity against infected macrophages.